PWE-112 Prevalence of osteoporosis in a Liverpool coeliac cohort supports routine use of bone mineral density assessment. (28th May 2012) - Collum, J; Smith, A; Martin, K
Abstract : Introduction: Coeliac disease may be associated with osteoporosis and increased fracture risk. Osteoporosis is a significant public health problem with major consequences for patients and health care systems. 1 Debate exists concerning the utility of routine bone mineral density (BMD) assessment in patients with coeliac disease. 2 We aimed to identify the prevalence of osteoporosis in patients with coeliac disease as defined by BMD assessment. Methods: Dietitian led data sets are currently maintained for all coeliac patients under active follow-up at University Hospital Aintree. We retrospectively analysed this information to determine (1) the frequency of BMD assessment in coeliac patients and, (2) the results of BMD assessment. Osteoporosis was defined as a T score of ≤−2.5 SDs below mean at either lumbar spine or hip. Results: The data sets for 232 patients were available for analysis. Demographics: 70% female, 30% male, mean age at diagnosis 52 (range 3–79 years). BMD assessment was undertaken in 211 (91%). The indication for this assessment in all cases was a clinicopathological diagnosis of coeliac disease. Of those undergoing BMD assessment, 26% had osteoporosis. On questioning at outpatient assessment 141 (67%) patients reported participation in regular weight bearing exercise. Of these patients 33 (24%) had osteoporosis compared to 10/30 (33%) not documented to undertake weight bearing exercise (p=0.26). Of those undergoing BMD assessment, 128 (61%) had been prescribed calcium supplements. 49/128 (38%) patients documented to be taking calcium supplements had BMD measurements consistent with osteoporosis compared to 4/82 (5%) patients not taking calcium supplements. Conclusion: At this UK centre, where over 90% of patients with coeliac disease underwent BMD assessment, 26% had osteoporosis. This is comparable to the rate demonstrated by Fitzgerald et al (25%) 3 and provides further support for the routine use of BMD assessment in coeliac disease to screen for osteoporosis. A lesser proportion of patients who participated in regular weight bearing exercise had osteoporosis at BMD assessment, but this finding was not statistically significant. Competing interests: None declared. References: 1. Lewis NR, Scott BB. Guidelines for Osteoporosis in Inflammatory Bowel Disease and Coeliac Disease. BSG Guidelines in Gastroenterology, 2007. http://www.bsg.org.uk/clinical-guidelines/ibd/guidelines-for-osteoporosis-in-inflammatory-bowel-disease-and-coeliac-disease.html 2. Lewis NR, Scott BB. Should patients with coeliac disease have their bone mineral density measured? Eur J Gastroenterol Hepatol 2005;17 :1065–70. 3. Fitzgerald T, Davies H, Howdle PD, et al. Prevalence of osteoporosis in Leeds coeliac cohort. Gut 2011;60 :A91.